Evaluating the impacts of transit-oriented developments (TODs) on household transportation expenditures in California - Dong, Hongwei (Journal of transport geography, 2021)
This study evaluates the impact of transit-oriented development (TOD) on household transportation expenditures in California by comparing TOD households with two groups of control households that are identified by propensity score matching. When controlling for household demographics, TOD households own fewer and more fuel-efficient cars, drive fewer miles, and use transit more. On average, they save $1232 per year on transportation expenditures than non-TOD households with similar demographics, accounting for 18% of their total annual transportation expenditures. When controlling for both demographics and neighborhood environment, TOD households still own slightly fewer and more fuel-efficient cars and use transit more. But they drive similar amount of miles as non-TOD households do. TOD households save $429 per year on transportation expenditures than non-TOD households with similar demographics and neighborhood environment, accounting for about 6% of their total annual transportation expenditures. TOD households save money on transportation costs mainly because they own fewer cars than non-TOD households. About two thirds of the savings can be attributed to transit-friendly neighborhood environment and one third to their access to rail transit, suggesting the importance of integrating a rail transit system with supportive land use planning and neighborhood design. •Californian households save $1232/year on transportation costs by living in TODs.•The savings accounts for 18% of their total transportation expenditures.•Neighborhood environment has a larger impact than access to rail transit.